Vasectomy and Prostate Cancer Incidence and Mortality in a Large US Cohort - Jacobs, Eric J. (J Clin Oncol, 2016)
PURPOSE: In a recent large prospective study, vasectomy was associated with modestly higher risk of prostate cancer, especially high-grade and lethal prostate cancer. However, evidence from prospective studies remains limited. Therefore, we assessed the associations of vasectomy with prostate cancer incidence and mortality in a large cohort in the United States. PATIENTS AND METHODS: We examined the association between vasectomy and prostate cancer mortality among 363,726 men in the Cancer Prevention Study II (CPS-II) cohort, of whom 7,451 died as a result of prostate cancer during follow-up from 1982 to 2012. We also examined the association between vasectomy and prostate cancer incidence among 66,542 men in the CPS-II Nutrition Cohort, a subgroup of the CPS-II cohort, of whom 9,133 were diagnosed with prostate cancer during follow-up from 1992 to 2011. Cox proportional hazards regression modeling was used to estimate multivariable-adjusted hazard ratios (HRs) and 95% CIs. RESULTS: In the CPS-II cohort, vasectomy was not associated with prostate cancer mortality (HR, 1.01; 95% CI, 0.93 to 1.10). In the CPS-II Nutrition Cohort, vasectomy was not associated with either overall prostate cancer incidence (HR, 1.02; 95% CI, 0.96 to 1.08) or high-grade prostate cancer incidence (HR, 0.91; 95% CI, 0.78 to 1.07 for cancers with Gleason score ≥ 8). CONCLUSION: Results from these large prospective cohorts do not support associations of vasectomy with either prostate cancer incidence or prostate cancer mortality.